Nf-LO: A Scalable, Containerized Workflow for Genome-to-Genome Lift Over. (12th August 2021) - Talenti, Andrea; Prendergast, James
Abstract: The increasing availability of new genome assemblies often comes with a paucity of associated genomic annotations, limiting the range of studies that can be performed. A common workaround is to lift over annotations from better annotated genomes. However, generating the files required to perform a lift over is computationally and labor intensive and only a limited number are currently publicly available. Here we present nf-LO (nextflow-LiftOver), a containerized and scalable Nextflow pipeline that enables lift overs within and between any species for which assemblies are available. nf-LO will consequently facilitate data interpretation across a broad range of genomic studies.